The Relationship Between Depression Symptoms Measured by The Patient Health Questionnaire-9 and Blood Sugar Levels in Type 2 Diabetes Mellitus Outpatient Patients at Raden Achmad Basoeni General Hospital, Mojokerto, East Java, 2025 - Shehnaz Neisa Rasyid; I Ketut Tirka Nandaka; Diah Purwaningsari (Journal of Social Research, 2026)
The purpose of this research was to determine the correlation of depressive symptoms in patients with T2DM on 2-hour postprandial (PP) blood sugar levels. This research was an analytical observational (quantitative) study with a cross-sectional design and a simple random sampling technique. This study was conducted at R.A Basoeni Regional General Hospital, Mojokerto, East Java. Depressive symptoms were measured using the Patient Health Questionnaire-9 (PHQ-9), while 2-hour PP blood sugar levels were measured using a glucometer conducted in July-August 2025 with 101 respondents. The data obtained were analyzed using the Chi-Square test to determine the correlation between the two variables. The results of this study indicate a significant correlation with p = 0.010 and ? = 0.05, which mean p < ?. Therefore, it can be concluded that there is a statistically significant relationship between depressive symptoms and 2-hour postprandial blood sugar levels in patients with T2DM. This finding confirms that depressive symptoms play a significant role in influencing blood sugar stability in patients with T2DM.